Theoretical study to calculate of the Ionization Constants of the Number of Amino Acid Derivatives using Quantum Mechanics Methods - Dr. Faiz M. AL-Abady; Noor H. Saeed (Kirkuk Journal of Science, 2017)
It was a theoretical study to calculated values of ionization constant of a group of amino acid derivatives using five methods of quantum mechanics for the purpose of comparison, two methods used semi empirical represented by a way of AM1, PM3 and the three methods used ab-initio basic calculation methods :HF, DFT and MP2, the compatibility of these methods with chemical bases known by discussing the theoretical variables were calculated by the five ways mentioned above, The results showed that the ab initio calculations were more accurate than semi empirical method which were created relationship between physical variables theoretically calculated with each other and determine their nature. Then link between these variables with known chemical values of amino acids ionization constants PK1. Results obtained through this relationship was good and that's what indicated to him the results of statistical analysis through correlation coefficient values, including the method of the DFT where it was (0.999) and the method of the PM3 (0.998) record and stander error (0.592), as well as the large overlap between PK1 values calculated theoretically with practical values. The difference of (0.008) for these results enables us to apply these variables in further studies.